DNA Mini-Barcoding: A Derived Barcoding Method for Herbal Molecular Identification - Gao, Zitong; Liu, Yang; Wang, Xiaoyue; Wei, Xuemin; Han, Jianping (Frontiers in Plant Science, 2019)
In recent years, demand for natural herbal products (NHP) has increased; however, the quality of these products is difficult to confirm due to the lack of a comprehensive quality control system. Traditional methods are not effective for detecting processed ingredients. DNA barcoding is an established technique that has been used for >10 years. This technique uses short standard sequences (generally 200–600 bp) to identify species. While a complete DNA barcode is difficult to obtain from NHP due to DNA degradation, mini-barcoding is a complementary tool to identify species in NHP. DNA mini-barcoding uses smaller DNA segments for polymerase chain reaction amplification, and can be applied to rapidly identify species. The present review summarizes the development and application of DNA mini-barcodes over recent years, and discusses the limitations of this technique. This review also compares mini-barcoding and meta-barcoding, a technique using universal polymerase chain reaction primers to simultaneously amplify multiple DNA barcodes and identify many species in a single environmental sample. Additionally, other detection methods that can be combined with mini-barcodes, such as nucleotide signatures, high-resolution DNA melting analysis, and gold nanoparticles, are discussed. DNA mini-barcoding can fill the gaps left by other methods in the field of herbal molecular identification.